Data Sharing across the Atlantic. - Veld, S.I (IEEE Security and privacy : building confidence in a networked world)
Government tend to be reluctant to submit their policies to democratic oversight, but in the US the Congress and the judiciary ultimately can and will hold the administration to account. Due to its constitutional peculiarities, however, Europe lacks adequate mechanisms for scrutinizing EU law enforcement and security policies: there's neither a European federal executive to hold accountable nor any way to hold the 27 member states' national governments to count for EU "federal" policies. Collecting each category of personal data might not individually constitute unacceptable violation at our privacy; but the cumulated measures of data collection and other observation mechanisms lead to a near complete surveillance of all citizens